2008
DOI: 10.1007/s10529-008-9884-1
|View full text |Cite
|
Sign up to set email alerts
|

High-yield production of erythritol from raw glycerol in fed-batch cultures of Yarrowia lipolytica

Abstract: An acetate-negative mutant of Yarrowia lipolytica Wratislavia K1 was selected that, when grown with 300 g raw glycerol l(-1) at pH 3, produced 170 g erythritol l(-1) after 7 days, corresponding to a 56% yield and a productivity of 1 g l(-1) h(-1). The Wratislavia K1 strain did not produce citric acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
107
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 179 publications
(123 citation statements)
references
References 15 publications
(18 reference statements)
9
107
3
Order By: Relevance
“…The application of crude glycerol at 13.3 Hz and 0.6 min -1 resulted in erythritol concentration of 58.2 g/L, yield of 0.38 g/g and productivity of 0.78 g/(L·h). On the other hand, Rymowicz et al (9) reported that in the fed-batch cultivation the application of crude glycerol (300 g/L) with Y. lipolytica Wratislavia K1 resulted in a higher concentration of erythritol (170 g/L) with the same yield of erythritol production of 0.56 g/g and lower productivity of 1.0 g/(L·h) than in the present study. Bett er results were obtained by Tomaszewska et al (13) when using the parental strain Y. lipolytica Wratislavia K1 in the fed-batch system with pulsed addition of glycerol (325 g/L).…”
Section: Eff Ect Of C:n Ratio On the Growth And Erythritol Productioncontrasting
confidence: 65%
See 3 more Smart Citations
“…The application of crude glycerol at 13.3 Hz and 0.6 min -1 resulted in erythritol concentration of 58.2 g/L, yield of 0.38 g/g and productivity of 0.78 g/(L·h). On the other hand, Rymowicz et al (9) reported that in the fed-batch cultivation the application of crude glycerol (300 g/L) with Y. lipolytica Wratislavia K1 resulted in a higher concentration of erythritol (170 g/L) with the same yield of erythritol production of 0.56 g/g and lower productivity of 1.0 g/(L·h) than in the present study. Bett er results were obtained by Tomaszewska et al (13) when using the parental strain Y. lipolytica Wratislavia K1 in the fed-batch system with pulsed addition of glycerol (325 g/L).…”
Section: Eff Ect Of C:n Ratio On the Growth And Erythritol Productioncontrasting
confidence: 65%
“…Batch or fed-batch cultures on glycerol are commonly used as systems for erythritol production, and therefore glycerol seems to be an effi cient substrate for this purpose (9,14). As reported before, in batch culture the same strain, Y. lipolytica MK1, was able to produce up to 82.2 g/L of erythritol from glycerol with yield of 0.55 g/g and productivity of 0.84 g/(L·h) (19).…”
Section: Eff Ect Of C:n Ratio On the Growth And Erythritol Productionmentioning
confidence: 61%
See 2 more Smart Citations
“…Y. lipolytica strain Wratislavia K1 co-produced citric acid (87-89 g/L) and erythritol (47 g/L) [112]. An interesting feature of strain K1 was its ability to selectively produce erythritol from CG [113]. Higher (71 g/L) citric acid yields from CG have also been reported [114].…”
Section: Other Bioproductsmentioning
confidence: 99%